2021
DOI: 10.1177/14680874211038729
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and design of real world driving cycles targeted to the calibration of vehicles with electrified powertrain

Abstract: Vehicles’ powertrain electrification is one of the key measures adopted by manufacturers in order to develop low emissions vehicles and reduce the CO2 emissions from passenger cars. High complexity of electrified powertrains increases the demand of cost-effective tools that can be used during the design of such powertrain architectures. Objective of the study is the proposal of a series of real-world velocity profiles that can be used during virtual design. To that aim, using three state of the art plug-in hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…There are pressure sensors in the hydraulic line, which monitor the fluid pressure and give constant feedback to the controller. The overall braking force is delivered by the friction and regenerative braking torque, which can be represented as in Equation (1), 168 normalTtotal demand=normalTregenerative+normalTfriction …”
Section: Regenerative Braking System Controller Outputsmentioning
confidence: 99%
“…There are pressure sensors in the hydraulic line, which monitor the fluid pressure and give constant feedback to the controller. The overall braking force is delivered by the friction and regenerative braking torque, which can be represented as in Equation (1), 168 normalTtotal demand=normalTregenerative+normalTfriction …”
Section: Regenerative Braking System Controller Outputsmentioning
confidence: 99%
“…However, they concluded that it is rather difficult to improve the thermal efficiency of the engine by these means. Doulgeris et al, 6 on the other hand, centered their study on the definition of specific real-world driving cycles to evaluate the overall energy efficiency of electrified powertrains.…”
Section: Special Issue: Thiesel 2020 Conference On Thermo-and Fluid-dynamic Processes In Direct Injection Enginesmentioning
confidence: 99%
“…In this sense, the THIESEL conference has always favored papers where the industrial implication is high. Four of the abovementioned papers are collaborative papers, either between a research center and a university, 3,6 or between an industrial company and a university. 2,9 To conclude, the papers selected from the THIESEL 2020 Conference for this special issue are a good sample of all relevant topics investigated nowadays to further improve engines efficiency and reduce emissions and fuel consumption…”
Section: Special Issue: Thiesel 2020 Conference On Thermo-and Fluid-dynamic Processes In Direct Injection Enginesmentioning
confidence: 99%
“…12 Powertrain electrification has been seen as a key solution in fleet decarbonisation with the development of Hybrid Electric Vehicles (HEVs), Plug-in Hybrid Electric Vehicles (PHEVs) and Battery Electric Vehicles (BEVs). [13][14][15][16] Electrified vehicles have gained significant market share in the last years and are an essential technical option to reduce CO 2 emissions. 17 However, powertrain electrification comes with a higher level of complexity due to the cohabitation of more power sources and numerous components.…”
Section: Introductionmentioning
confidence: 99%